Seasonal Sulfur Biogeochemistry of Oil Sands Composite Tailings Undergoing Fen Reclamation - Stephenson, Kate E. (My University, 2012)
The Athabasca oil sands produce 20% of Canada’s oil, which in turn creates trillions of cubic meters of waste. The Alberta government mandates that oil sands land be reclaimed to its natural state after mining has occurred. Syncrude Canada is currently creating a novel freshwater fen on top of a composite tailings (CT) deposit as a pilot large-scale reclamation project. CT are both microbially and sulfur rich, in addition, the fen could be a potential source of labile organics and sulfate reducing bacteria which could further stimulate sulfur cycling by microorganisms with the potential to stimulate H2S(g) generation, a health and safety concern. Therefore, this thesis examines three main research questions regarding this H2S production within the Sandhill reclamation fen: 1) Is H2S generation widespread within the porewaters of the CT and sand cap of the developing Sandhill Fen reclamation project? 2) Do microbial metabolisms capable of metabolizing Fe and S linked to H2S generation occur within CT and sand cap of the developing Sandhill Fen? and 3) Will seasonality and ongoing fen construction impact H2S generation?
Field and experimental results herein discuss potential microbial and abiotic metabolisms and pathways that effect sulfur and iron cycling that could affect hydrogen sulfide generation within the composite tailings and developing fen during three seasonal sampling campaigns from June 2010 to July 2011. Results indicate that detectable H2S(aq) occurred in the fen porewaters during each sampling campaign, with a trend of increasing H2S(aq) concentrations as construction of the fen progressed. Further, enrichment results indicate that microbial sulfur and iron redox reactions are likely affecting the H2S(aq) generation. Experimental microcosm results indicate that the CT may contain unstable sulfur species that can contribute to H2S(aq) generation and sequestration in the CT as pyrite. Additionally, the evolution of the Sandhill Fen changed the microbial communities that were present in situ as well as shifted dominance of species type in environmental microbial enrichments. The putative function of these bacteria show a shift from autotrophy to increased heterotrophic metabolisms as the fen is being constructed, suggesting the addition of labile organic substrates from the peat and woody debris are both changing the dominant metabolisms and well as increasing microbial diversity to the underlying CT and sand cap of Sandhill Fen. Results of this thesis established widespread microbial Fe and S metabolisms within CT for the first time and indicated that fen reclamation will alter microbial activity with implications for S cycling within CT. Although this thesis covers a short sampling time frame, it is clear that H2S(aq) generation is an important factor to consider during large scale CT reclamation. While microorganisms are present and could be impacting Fe and S cycling, the CT materials should be investigated further in regards to their potential for H2S(aq) generation. More consideration should be given to inhibiting H2S(aq) generation or supporting FeS formation within the reclamation fen.
Keywords: composite tailings; sulfur; iron; biogeochemistry; oil sands; hydrogen sulphide; Environmental Sciences; Environmental Sciences